Nine lies about work : a freethinking leader's guide to the real world - Buckingham, Marcus; Goodall, Ashley (Author of Nine lies about work) (Boston, Massachusetts : Harvard Business Review Press, 2019)
How do you get to what's real? Your organization's culture is the key to its success. Strategic planning is essential. People's competencies should be measured and their weaknesses shored up. People crave feedback. These may sound like basic truths of our work lives today. But actually, they're lies. As strengths guru and bestselling author Marcus Buckingham and Cisco Leadership and Team Intelligence head Ashley Goodall show in this provocative, inspiring book, there are some big lies--distortions, faulty assumptions, wrong thinking--running through our organizational lives. Nine lies, to be exact. They cause dysfunction and frustration and ultimately result in a strange feeling of unreality that pervades our workplaces. But there are those who can get past the lies and discover what's real. These are freethinking leaders who recognize the power and beauty of our individual uniqueness, who know that emergent patterns are more valuable than received wisdom, and that evidence is more powerful than dogma. With engaging stories and incisive analysis, the authors reveal the essential truths that such freethinking leaders will recognize immediately: that it is the strength and cohesiveness of your team, not your company's culture, that matters most; that we need less focus on top-down planning and more on giving our people reliable, real-time intelligence; that rather than trying to align people's goals we should strive to align people's sense of purpose and meaning; that people don't want constant feedback, they want helpful attention. This is the real world of work.--
Lie #1. People care which company they work for -- Lie #2. The best plan wins -- Lie #3. The best companies cascade goals -- Lie #4. The best people are well-rounded -- Lie #5. People need feedback -- Lie #6. People can reliably rate other people -- Lie #7. People have potential -- Lie #8. Work-life balance matters most -- Lie #9. Leadership is a thing -- Truths.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed February 18, 2019).
Added to collection customer.56279.3
Keywords: Organizational effectiveness; Industrial management; Organizational change; Industrial management; Organizational change; Organizational effectiveness; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; elektronické knihy; electronic books